Adrenomedullin in heart failure: pathophysiology and therapeutic application. (28th December 2018) - Voors, Adriaan A.; Kremer, Daan; Geven, Christopher; ter Maaten, Jozine M.; Struck, Joachim; Bergmann, Andreas; Pickkers, Peter; Metra, Marco; Mebazaa, Alexandre; Düngen, Hans‐Dirk; Butler, Javed
Abstract : Adrenomedullin (ADM) is a peptide hormone first discovered in 1993 in pheochromocytoma. It is synthesized by endothelial and vascular smooth muscle cells and diffuses freely between blood and interstitium. Excretion of ADM is stimulated by volume overload to maintain endothelial barrier function. Disruption of the ADM system therefore results in vascular leakage and systemic and pulmonary oedema. In addition, ADM inhibits the renin–angiotensin–aldosterone system. ADM is strongly elevated in patients with sepsis and in patients with acute heart failure. Since hallmarks of both conditions are vascular leakage and tissue oedema, we hypothesize that ADM plays a compensatory role and may exert protective properties against fluid overload and tissue congestion. Recently, a new immunoassay that specifically measures the biologically active ADM (bio‐ADM) has been developed, and might become a biomarker for tissue congestion. As a consequence, measurement of bio‐ADM might potentially be used to guide diuretic therapy in patients with heart failure. In addition, ADM might be used to guide treatment of (pulmonary) oedema or even become a target for therapy. Adrecizumab is a humanized, monoclonal, non‐neutralizing ADM‐binding antibody with a half‐life of 15 days. Adrecizumab binds at the N‐terminal epitope of ADM, leaving the C‐terminal side intact to bind to its receptor. Due to its high molecular weight, the antibody adrecizumab cannot cross the endothelial barrier and consequently remains in the circulation. The observation that adrecizumab increases plasma concentrations of ADM indicates that ADM‐binding by adrecizumab is able to drain ADM from the interstitium into the circulation. We therefore hypothesize that administration of adrecizumab improves vascular integrity, leading to improvement of tissue congestion and thereby may improve clinical outcomes in patients with acute decompensated heart failure. A phase II study with adrecizumab in patients with sepsis is ongoing and a phase II study on the effects of adrecizumab in patients with acute decompensated heart failure with elevated ADM is currently in preparation.